Undiagnosed fibromuscular dysplasia in a deceased donor kidney transplant successfully treated with angioplasty. Issue 10 (22nd October 2020) - Medeiros, Edward; Gohh, Reginald; Merhi, Basma
Abstract : A 41-year-old man with end-stage renal disease received a deceased donor kidney transplant without complication. Maintenance immunosuppression consisted of tacrolimus, mycophenolate and prednisone. Two months after transplantation, his creatinine did not improve beyond 2–2.3 mg/dL, which prompted allograft biopsy. His biopsy showed tubular epithelial injury without rejection, and given concern for possible calcineurin-inhibitor toxicity, his tacrolimus was changed to sirolimus. Renal function improved, but 1 month later he presented to the hospital with seizure activity, severe hypertension, acute kidney injury and MRI findings suggestive of posterior reversible encephalopathy syndrome. Blood pressure was difficult to control, which had not been the case in the immediate posttransplant period, and addition of lisinopril worsened his renal function. Transplant renal artery stenosis was suspected, and allograft ultrasound with doppler confirmed our suspicion. The patient underwent an angiogram, showing 60% stenosis of the mid-distal transplanted renal artery. Interventional radiology successfully stented this lesion, with subsequent improvement in allograft function and blood pressure control. He did not require further intervention in follow-up.